Diabetes Attitudes, Wishes and Needs second study (DAWN2™): Cross‐national benchmarking indicators for family members living with people with diabetes. Issue 7 (23rd June 2013) - Kovacs Burns, K.; Nicolucci, A.; Holt, R. I. G.; Willaing, I.; Hermanns, N.; Kalra, S.; Wens, J.; Pouwer, F.; Skovlund, S. E.; Peyrot, M.; ,
Abstract Aims The second Diabetes Attitudes, Wishes and Needs (DAWN2) study examined the experiences of family members of people with diabetes for benchmarking and identifying unmet needs or areas for improvement to assist family members and those with diabetes to effectively self‐manage. Methods In total, 2057 family members of people with diabetes participated in an online, telephone or in‐person survey designed to assess the impact of diabetes on family life, family support for people with diabetes and educational and community support. Results Supporting a relative with diabetes was perceived as a burden by 35.3% (range across countries 10.6–61.7%) of respondents. Over half of respondents [51.4% (22.5–76.0%)] rated their quality of life as 'good' or 'very good'. However, distress about the person with diabetes was high, with 61.3% (31.5–86.4%) worried about hypoglycaemia. The impact of diabetes on aspects of life was felt by 51.8% (46.9–58.6%). The greatest negative effect was on emotional well‐being [44.6% (31.8–63.0%)], although depression was less common [11.6% (4.2–20.0%)]. Many respondents did not know how to help the person with diabetes [37.1% (17.5–53.0%)] and wanted to be more involved in their care [39.4% (15.5–61.7%)]. Participation in diabetes educational programmes was low [23.1% (9.4–43.3%)], although most of those who participated found them helpful [72.1% (42.1–90.3%)]. Conclusions Diabetes has a negative impact on family members of people with diabetes. DAWN2 provides benchmarking indicators of family members' psychosocial needs that will help identify the support required for, and from, them to improve the lives of people with diabetes and their families.